Self-assembly of E. coli MutL and its complexes with DNA - Niedziela-Majka, Anita (2011)
The E. coli MutL protein regulates the activity of several enzymes, including MutS, MutH and UvrD, during methyl-directed mismatch repair (MMR) of DNA. We have investigated the self association properties of MutL and its binding to DNA using analytical sedimentation velocity and equilibrium. Self association of MutL is quite sensitive to solution conditions. At 25°C in Tris at pH 8.3 MutL assembles into a heterogeneous mixture of large multimers. In the presence of potassium phosphate at pH 7.4, MutL forms primarily stable dimers, with the higher order assembly states suppressed. The weight averaged sedimentation coefficient of MutL dimer in this buffer is equal to s̅(20,w) = 5.20 ± 0.08, suggesting a highly asymmetric dimer (f/f(o) = 1.58 ± 0.02). Upon binding the non-hydrolyzable ATP analogue, AMPPNP/Mg(2+), the MutL dimer becomes more compact (s̅(20,w) = 5.71 ± 0.08 S, f/f(o) = 1.45 ± 0.02), probably reflecting reorganization of the N-terminal ATPase domains. A MutL dimer binds to an 18 bp duplex with a 3’-(dT(20)) single stranded flanking region, with apparent affinity in the micromolar range. AMPPNP binding to MutL increases its affinity for DNA by a factor of ~10. These results indicate that the presence of phosphate minimizes further MutL oligomerization beyond a dimer and that differences in solution conditions likely explain apparent discrepancies in previous studies of MutL assembly.